Mammalian Models of Traumatic Brain Injury and a Place for Drosophila in TBI Research - Shah, Ekta J.; Gurdziel, Katherine; Ruden, Douglas M. (Frontiers in Neuroscience, 2019)
Traumatic brain injury (TBI), consisting of damage caused by a blow or jolt that disrupts normal brain function (1), is an emerging health epidemic with ~2.5 million cases occurring annually in the USA that are severe enough to cause hospitalization or death (2). Most common causes of TBI include contact sports, vehicle crashes, domestic violence or war injuries (3). TBI is one of the most consistent candidates for initiating the molecular and cellular cascades that result in Alzheimer’s disease (AD), Parkinson’s disease (PD), Chronic traumatic encephalopathy (CTE) and Amyotrophic lateral sclerosis (ALS) (4). Not every TBI event is alike with effects varying from person to person. The majority of people recover from mild TBI within a short period of time but repeated incidents can have deleterious long-lasting effects which depend on factors such as the number of TBI’s sustained, time till medical attention, age, gender and genetics of the individual (5). Despite extensive research many questions still remain regarding diagnosis, treatment and prevention of long-term effects from TBI as well as recovery of brain function. In this review, we discuss using Drosophila melanogaster as a model to study TBI (6) and outline the current TBI inducing methods used to inflict brain trauma. The relatively small brain sized (~100,000 neurons and glia), conserved neurotransmitter signaling mechanisms, and sophisticated genetics of Drosophila melanogaster allows for cell biological, molecular, and genetic analyses that are impractical in mammalian models of TBI.